Severe myocardial injury in an infant with hemorrhagic shock and encephalopathy syndrome - Kendirli, Tanil; Gümüs, Derya; Öztürk, Burcu; Ince, Erdal; Deda, Gülhis; Tutar, Ercan (Journal of Pediatric Neurology, 2005)
Hemorrhagic shock and encephalopathy syndrome is a severe disease that affects previously healthy infants and associated with significant mortality and neurologic morbidity. It is characterized by sudden onset of shock, convulsion and coma, bleeding due to severe coagulopathy, fever, diarrhea, metabolic acidosis, and hepatorenal dysfunction. We report a 3-month-old boy with hemorrhagic shock and encephalopathy syndrome, who had clinical and laboratory findings consistent with myocardial injury. Severe myocardial injury was demonstrated by elevation of cardaic troponin I and MB fraction of total kinase in this patient.
Keywords: Hemorrhagic shock encephalopathy syndrome; myocardial injury; cardiac troponin I